2019
DOI: 10.4252/wjsc.v11.i9.618
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane and bioactive factors derived from mesenchymal stromal cells: Cell-free based therapy for inflammatory bowel diseases

Abstract: Inflammatory bowel diseases (IBD) are chronic inflammatory disorders of the gastrointestinal tract associated with multifactorial conditions such as ulcerative colitis and Crohn's disease. Although the underlying mechanisms of IBD remain unclear, growing evidence has shown that dysregulated immune system reactions in genetically susceptible individuals contribute to mucosal inflammation. However, conventional treatments have been effective in inducing remission of IBD but not in preventing the relapse of them.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 145 publications
(206 reference statements)
0
4
0
Order By: Relevance
“…PD‐L1 and TNFL6 are two well‐known immunomodulatory ligands on MSCs that are known to inhibit adaptive T cell immune response through cell‐cell contact. [ 18,28 ] We first confirmed the presence of PD‐L1 and TNFL6 on intact MSCs using flow cytometry (Figure 1d). Consistent with our hypothesis, IFN‐γ priming significantly increased the expression level of PD‐L1 and TNFL6, compared to naïve MSCs.…”
Section: Resultsmentioning
confidence: 77%
“…PD‐L1 and TNFL6 are two well‐known immunomodulatory ligands on MSCs that are known to inhibit adaptive T cell immune response through cell‐cell contact. [ 18,28 ] We first confirmed the presence of PD‐L1 and TNFL6 on intact MSCs using flow cytometry (Figure 1d). Consistent with our hypothesis, IFN‐γ priming significantly increased the expression level of PD‐L1 and TNFL6, compared to naïve MSCs.…”
Section: Resultsmentioning
confidence: 77%
“…Recent studies have shown that MSC-EVs can improve the recovery of damaged tissues [84], and identified 730 proteins by LC coupled MS/MS analysis, 43 surface receptors as well as signaling molecules are characterized, which is responsible for self-renewal and differentiation. Some other analysis indicated that MSCs-EVs proteins contributed to cell proliferation, migration, adhesion, and morphogenesis [88,89]. Self-renewal ability and differentiation potentiality of MSCs can be associated with the therapeutic effects, which is regulated by the integration of related genes, including signaling molecules (CDC42, VAV2); surface receptors (PDGFRB, EGFR, and PLAUR); antigens (CD109, CD248, CD151 and CD276) [84].…”
Section: Ev Componentsmentioning
confidence: 99%
“…However, their poor post-transplant cell survival rate, complications, and other ethical issues hinder clinical application [11,12]. Recent studies reported that the efficacy of MSCs is mainly attributed to their paracrine action on the improvement of the local microenvironment [13][14][15]. Previous findings also indicated that ecto-mesenchymal stem cells-conditional medium (EMSCs-CM) with potent anti-inflammation potential has therapeutic effects on colitis [16].…”
Section: Introductionmentioning
confidence: 99%